Both‐In‐One Rapid Detection and Removal of Methylmercury in Real Complex Aquatic Environments Using a Janus Confined SERS Filter Membrane - Guo, Xiao; Cai, Xin; Lei, Fengcai; Jiao, Yang; Zhao, Xiaofei; Li, Zhen; Zhang, Chao; Man, Baoyuan; Yu, Jing (Advanced functional materials, 2025)
A surface‐enhanced Raman scattering (SERS) filter membrane based on a Janus copper/poly(vinylidene fluoride)/zinc oxide/silver/zeolitic imidazolate framework‐8 (Cu/PVDF/ZnO/Ag/ZIF‐8, J‐CPZAZ) is designed in this work, which can extract and enrich methylmercury (MeHg) from real samples containing various sizes and types of interferents into the PVDF/ZnO/Ag/ZIF‐8 SERS enhancement unit directly within 2 min. Combined with the microcavity structure in PVDF/ZnO/Ag/ZIF‐8, J‐CPZAZ can also localize the incident light at the same position. This co‐confinement effect of “hotspot‐molecule” effectively lowers the limit of detection of MeHg to 10−10 m. Interestingly, a controllable wettability of J‐CPZAZ endows it with good oil‐water separation function for separating various kinds of MeHg extractant (>95%) from mixed aqueous solution. Based on these features, a dual‐layer J‐CPZAZ filter membrane is further successfully fabricated, enabling both‐in‐one detection and removal of MeHg from real water environments. In the experiments, real water samples are selected from six different water areas in Shandong Province, China, for relevant tests and compared the results with those obtained using traditional gas chromatography. The results demonstrate that the dual‐layer J‐CPZAZ filter membrane exhibits both high MeHg removal efficiency (≈100%) and detection accuracy (average error < 1.8%), showcasing great application potential. This work addresses the issue of methylmercury (MeHg) contamination in real complex aquatic environments by designing a surface‐enhanced Raman scattering (SERS) filter membrane with both rapid detection and removal capabilities for MeHg.